Anodal Transcranial Direct Current Stimulation Can Improve Spatial Learning and Memory and Attenuate Aβ42 Burden at the Early Stage of Alzheimer’s Disease in APP/PS1 Transgenic Mice - Luo, Yinpei; Yang, Wenjuan; Li, Nian; Yang, Xiufang; Zhu, Binglian; Wang, Cong; Hou, Wensheng; Wang, Xing; Wen, Huizhong; Tian, Xuelong (Frontiers in Aging Neuroscience, 2020)
Alzheimer's disease (AD) is an irreversible progressive neurodegenerative disease. Intervention in the early stage of AD is a new path for AD treatment that is being explored. The behavioral and pathological effects of anodal transcranial direct current stimulation (AtDCS) at the early stage of AD in the mouse model, amyloid precursor protein (APP)/presenilin-1 (PS1) transgenic mice, were investigated based on our previous studies. Thirty-three 6-month-old male APP/PS1 mice were randomly divided into the model group (AD group), model + sham stimulation group (ADST group) and stimulation group (ADT group). Eleven 6-month-old male C57 wild-type mice were randomly selected as a control group (CTL group). The ADT group received 10 AtDCS sessions. The Morris water maze (MWM) task and novel object recognition (NOR) task were used to test mouse memory. Nissl staining, Western blot (WB), immunohistochemistry and immunofluorescence staining of β-amyloid (Aβ42), glial fibrillary acidic protein (GFAP) and NF200 were conducted for pathological analysis. The ADT group and the CTL group had a shorter escape latency and more platform-region crossings than the AD group and ADST group in the MWM. There was no significant difference in the discrimination index among the groups in the NOR task. Pathological analysis showed visible differences between the AD group and ADT group. This study revealed that early-stage APP/PS1 transgenic mice did not show recognition memory impairment. AtDCS effectively improved spatial learning and memory in the early-stage APP/PS1 transgenic mouse model of AD, alleviating Aβ burden and having a protective effect on neurons. AtDCS could improve AD-related symptoms by activating many glial cells to promote the degradation and clearance of Aβ or directly affecting production and degradation of Aβ to reduce glial activation. AtDCS is an effective means of early intervention in the early stage of AD.